Interplay Between Desiccation and Oxidative Stress Responses in Iron-Oxidizing Acidophilic Bacteria - Levican-Jaque, G; Muñoz-Villagran, C (Elsevier B.V., 2024)
Variations in water availability represent a foremost stress factor affecting the growth and survival of microorganisms. Acidophilic bioleaching bacteria are industrially applied for releasing metals from mineral sulphides, and they are considered extremely tolerant to oxidative conditions prevailing in acidic bioleaching environments. Such processes usually are performed in heaps and thus these microorganisms are also exposed to intermittent desiccations or high osmolarity periods that reduce the water availability. However, the tolerance to water stress and the molecular basis of adaptation to it are still largely unknown. The aim of this work was to determine the cellular response to desiccation stress and establish its relationship to oxidative stress response in the acidophilic iron-oxidizing bacteria Acidithiobacillus ferrooxidans ATCC 23270 and Leptospirillum ferriphilum DSM 14647. Results showed that the exposure of cell cultures to desiccation (0–120 min) led to a significant reduction in cell growth, and to an increase in content in reactive oxygen species in both bacteria. However, Leptospirillum ferriphilum turned out to be more tolerant than Acidithiobacillus ferrooxidans. In addition, the pre-treatment of the cell cultures with compatible solutes (trehalose and ectoine), and antioxidants (glutathione and cobalamin) restored all stress parameters to levels exhibited by the control cultures. To evaluate the role of the osmotic and redox homeostasis mechanisms in coping with desiccation stress, the relative expression of a set of selected genes was approached by RT-qPCR experiments in cells exposed to desiccation for 30 min. Results showed a generalized upregulation of genes that code for mechanosensitive channels, and enzymes related to the biosynthesis of compatible solutes and oxidative stress response in both bacteria. These data suggest that acidophiles show variable tolerance to desiccation and allow to establish that water stress can trigger oxidative stress, and thus anti-oxidative protection capability can be a relevant mechanism when cells are challenged by desiccation or other anhydrobiosis states. © 2024 Elsevier B.V.